2018
DOI: 10.4038/seajme.v12i2.50
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the choice of postgraduate specialty among undergraduate medical students: a prospective observational study from India

Abstract: National policies on the number and distribution of post graduate seats in medical colleges are based on estimated projections of the quantum need of medical work force in the country in future. In order to attract talent, it is imperative to know what factors, modifiable or non modifiable, affect the choice of specialization.Methods: This is a cross-sectional, observational study. Subjects were undergraduate medical students, at four different phases of their course. They were asked to fill an anonymous feedb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…19,23,24 Chawla et al found that passion for the subject and financial gain were the main reasons behind specialty selection. 3 The most stated reasons behind specialty preference in studies conducted in Kuwait included looking for a good treatment outcome for patients, the presence of interesting cases, and the ability to maintain long-term relationships in the discipline 6 . A study conducted among female students in Taif University, Saudi Arabia stated that the first reason behind specialty selection was career development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19,23,24 Chawla et al found that passion for the subject and financial gain were the main reasons behind specialty selection. 3 The most stated reasons behind specialty preference in studies conducted in Kuwait included looking for a good treatment outcome for patients, the presence of interesting cases, and the ability to maintain long-term relationships in the discipline 6 . A study conducted among female students in Taif University, Saudi Arabia stated that the first reason behind specialty selection was career development.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 The tendency toward the selection of different medical specialties can largely influence the future landscape of the physician workforce in a healthcare system. 3 Failure to adopt the right strategies to plan and adjust the medical specialties selection may lead to undesirable consequences for health systems, one of which is the imbalance between various specialties. 4 This inadequate future planning may lead to a lack of health services in future specialties in the rural areas, while the primary health services will take the most part of it.…”
Section: Introductionmentioning
confidence: 99%
“…However, except for limited literature available in this regard, there is still a dearth of studies on particular subjects chosen by students at the PG level, except a few on medical students (e.g. Chawla et al, 2018).…”
Section: Theoretical Framework 21 Choice Of a Subject At Pg Levelmentioning
confidence: 99%
“…Although the determinants that affect specialty preference are generally similar across different countries, there are some differences resulting from country-specific factors and healthcare systems. For instance, in certain countries, gender and family influence can also be significant determinants [ 7 ].…”
Section: Introductionmentioning
confidence: 99%